Association of simvastatin use with glycemic control in type 2 diabetes patients receiving oral antihyperglycemic therapy and in non-diabetic subjects / Nor Razida Razali - Nor Razida, Razali (2018)
Previous evidence shows the conflicting effect of simvastatin on glycemic control on type 2 diabetes (T2D) patients. Although the lipid-lowering benefits of simvastatin have been shown to outweigh the risks, its potential impact on glycemic control in T2D is a major concern. Moreover, the effects of statins on glycemic control in T2D patients with multiple co-morbidities and other concomitant drugs have not been fully elucidated. The purpose of this study is to evaluate the association of simvastatin use on glycemic control in T2D patients receiving oral antihyperglycemic drugs (OADs) and compared it with simvastatin users without diabetes. This retrospective cross-sectional study was conducted at University Malaya Medical Centre (UMMC) Kuala Lumpur. The glycemic control was indicated by fasting plasma glucose (FPG) and glycated hemoglobin (A1C). A total of 418 eligible patients were included in this study with 209 patients in the diabetic and the non-diabetic groups respectively. The mean duration of simvastatin use in diabetic was 11.3 ± 6.54 months whilst the non-diabetic group was 11.7 ± 7.03 months. This study found that T2D patients did not experience the impairment of glycemic control whilst on statins, compared to the non-diabetes patients. In the diabetic group, the FPG levels had significantly decreased from 7.10 ± 1.49 mmol/L to 6.87 ± 1.41 mmol/L post simvastatin therapy (p = 0.041). The same trends were observed in A1C levels with a reduction from 7.18 ± 1.04% at the pre-simvastatin therapy to 6.98 ± 1.05% after the simvastatin therapy (p < 0.001). In contrast, the glycemic control in the non-diabetic group was significantly impaired with an increase in the FPG levels from 5.40 ± 0.66 mmol/L at the presimvastatin therapy to 5.51 ± 0.68 mmol/L post-therapy (p = 0.026) respectively. Besides that, the A1C levels at post simvastatin therapy 5.76 ± 0.5% was significantly higher iv compared to pre-therapy 5.69 ± 0.46% (p = 0.014). Furthermore, in the diabetic group, the results showed a positive correlation between the changes in the triglyceride levels and FPG (r = 0.219, p = 0.014); triglyceride levels and A1C (r = 0.242, p = 0.007) and a negative correlation between the changes in high density lipoprotein (HDL) cholesterol and A1C levels (r = - 0.189, p = 0.030). The correlate model indicated that the decreasing of triglyceride levels in the diabetic group was associated with the decreasing levels in FPG (β = 0.22, t = 2.37, p = 0.019) and A1C (β = 0.24, t = 2.64, p = 0.009). This study proposed that the reduction of triglyceride levels in T2D patients on oral antihyperglycemic therapy after commencing simvastatin therapy was associated with the improvement in glycemic control. The correlates models suggested that in the T2D patients the decrease in triglyceride levels may be associated with the improvement of glucose parameters, indicating that the management treatments for both glycemic control and lipid profile may play a crucial role to achieve the targeted glycemic levels following statins initiation.